Atypical presentation of Lyme neuroborreliosis related meningitis and radiculitis - Iman Dabiri (Neurology International, 2019)
Lyme disease related central and peripheral nervous system manifestations can occur in isolation or together. Radiculitis or inflammation of the nerve root can be seen 3-5% of the time in acute neuroborreliosis affecting the PNS with a typical presentation and meningitis affecting the CNS is usually seen 1% of the time. The appropriate diagnosis and management of neuroborelliosis can be challenging and require meticulous medical approaches. Herein we present a unique case of Lyme disease with neurologic manifestations including both radiculitis and meningitis due to its atypical and challenging clinical presentation and management with updated literature review.